2017
DOI: 10.1113/ep086336
|View full text |Cite
|
Sign up to set email alerts
|

Passive heat stress reduces circulating endothelial and platelet microparticles

Abstract: What is the central question of this study? Does passive heat stress of +2°C oesophageal temperature change concentrations of circulating arterial endothelial- and platelet-derived microparticles in healthy adults? What is the main finding and its importance? Concentrations of circulating endothelial- and platelet-derived microparticles were markedly decreased in heat stress. Reductions in circulating microparticles might indicate favourable vascular changes associated with non-pathological hyperthermia. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 41 publications
2
36
3
Order By: Relevance
“…Indeed, we have previously demonstrated that acute passive hyperthermia of +2°C core temperature causes a reduction in the concentration of circulating pro‐oxidative microparticles (Bain et al . ). Moreover, although IL‐6 is generally considered a sign of neural inflammation (Erta et al .…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, we have previously demonstrated that acute passive hyperthermia of +2°C core temperature causes a reduction in the concentration of circulating pro‐oxidative microparticles (Bain et al . ). Moreover, although IL‐6 is generally considered a sign of neural inflammation (Erta et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, a recent study reported that acute passive heat stress reduces circulating levels of endothelial‐ and platelet‐derived microparticles (Bain et al . ). Elevated circulating levels of these particles are known to promote endothelial oxidative stress (Burger et al .…”
Section: Discussionmentioning
confidence: 97%
“…A recent publication, however, reported reductions in arterial [PMV] (CD62P + – P‐selectin) in young men exposed to acute whole‐body passive heat stress, which elevated core temperature by +2°C (Bain et al. ). Currently, it is difficult to identify the reasons for such contradictory findings, but it may relate to the different sample preparation and storing protocols, distinct flow cytometer size resolution differences between studies, and the specificity of markers used for microvesicle population identification.…”
Section: Discussionmentioning
confidence: 99%
“…To adequately determine the impact of heat stress upon circulating [PMV], future studies need to assess the PMV time course with passive heat stress to establish whether the PMV concentrations increase initially, and then decline with higher levels of hyperthermia as suggested by Bain et al. ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation